IMPLEMENTASI STRATEGI PEMASARAN HANDICRAFT BAGI UMKM DI BANYUWANGI - Dilla Cattleyana; Khoirun Drasti Kirana Putri (LPPM STIE Muhammadiah Bandung, 2022)
The purpose of this study was to determine the simultaneous and partial effect of the quality of sales promotion, facilities and location toward purchasing decisions at handicraft from SMEs in Banyuwangi. This research used quantitative approach. The results showed that simultaneously the quality of sales promotion (X1), facilities (X2) and location (X3) had a significant effect on purchasing decisions (Y), which was indicated by the value of Fcount = 30,681 > Ftable = 2,70 and partially all independent variables had a significant effect to the dependent variable, which was indicated by the values of tcount > ttable. This study delivered a suggestion that there is a need to improve facilities in the future and maximize marketing management to be more optimal. Thus, purchasing decisions are also increasing and it will also affect the progress of the company.